A atitude como fator de adoção de tecnologia: propondo um modelo de análise de atitudes, para auxiliar em estratégias de inclusão digital, aplicado a comunidades próximas a telecentros da prefeitura de São Paulo - Galery, Augusto Dutra (2005)
Technology has had a crucial role in the development of Societies since the beginning of Mankind. Nowadays, this role is occupied by the Digital Economy and, for this reason, Digital Divide is the target of special attention for the whole society. This theme is viewed, especially, by two prisms: mass access to computers and the Internet, and know-how to use it. However in order for Digital Inclusion to take place the reasons why an individual adopt a specific technology must be studied. Attitude – a group of believes and cognitions with an emotional quantum, put together by the social context, driving to a certain behavior – in relation to technology it could be a good way to know which type of strategy must be taken to drive an individual to adopt it, which could help the efforts to decrease Digital Divide. To study attitudes, a projective pictorial technique is proposed and the content of the answers is analyzed, to categorize the sample in different groups. The Personal computer was chosen as an attitudinal object, and the sample was taken in communities near Sao Paulo City Hall´s free access computer centers The results of content analyses showed that there is a concentration of answers related to: computer usage, learning how to use it and, at a minor rate, the relationship between computers and jobs. Neutral and escaping answers are present, too. The sample has been segmented, in relation to the answer form, as affirmative, interrogative and imperative answers. Crossing these categories and the frequency of usage it was possible to divide the sample, into subgroups which would permit the design of specific strategies for each of them. It was also possible to delineate the content of the strategies and to determine which subgroups must be focused first.